2017
DOI: 10.1109/jlt.2016.2615815
|View full text |Cite
|
Sign up to set email alerts
|

Reach Extension and Capacity Enhancement of VCSEL-Based Transmission Over Single-Lane MMF Links

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In addition, various standards groups are in the process of defining serial 100 Gb s −1 electrical interfaces, including the copper PCB and cable channels [223,224]. Regarding multimode fibre (MMF) and VCSEL-based transmitters, recent papers have shown that with IM/DD and PAM4 modulation, 100 Gb s −1 per lane could be supported [225,226,227]. As it might be difficult to achieve enough bandwidth to enable 100 Gb s −1 NRZ via direct modulation, VCSELs with integrated modulators are being investigated [228].…”
Section: Challenges For the Futurementioning
confidence: 99%
“…In addition, various standards groups are in the process of defining serial 100 Gb s −1 electrical interfaces, including the copper PCB and cable channels [223,224]. Regarding multimode fibre (MMF) and VCSEL-based transmitters, recent papers have shown that with IM/DD and PAM4 modulation, 100 Gb s −1 per lane could be supported [225,226,227]. As it might be difficult to achieve enough bandwidth to enable 100 Gb s −1 NRZ via direct modulation, VCSELs with integrated modulators are being investigated [228].…”
Section: Challenges For the Futurementioning
confidence: 99%
“…HE short-reach optical links based on 850 nm GaAsbased VCSELs over up to 100 m multimode fibers (MMF) have been widely deployed in large scale data centers [1], [2], [3]. However, the high chromatic dispersion of fiber and attenuation at this wavelength are important factors limiting transmission distance [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The short-reach optical interconnects used in data centers are dominated by 850 nm GaAs-based vertical-cavity surfaceemitting lasers (VCSELs) and multimode fiber (MMF) links, typically reaching up to 100 meter in link length [1][2][3]. However, the distance is fundamentally limited by the high chromatic dispersion of fiber and attenuation at this wavelength [4,5].…”
Section: Introductionmentioning
confidence: 99%